Insight into water oxidation activity enhancement of Ni-based electrocatalysts interacting with modified carbon supports - Lee, Si Young; Jung, Hyejin; Chae, Sang Youn; Oh, Hyung-Suk; Min, Byoung Koun; Hwang, Yun Jeong (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Water splitting is a clean and renewable way to produce hydrogen, and developing an efficient water oxidation electrocatalyst is crucial to overcome the slow kinetics and large overpotential of the oxygen evolution reaction (OER) in water electrolysis. In this work, we demonstrate that OER activity of an electrodeposited Ni catalyst can be influenced by a support material, and electron transfer between the Ni-based catalyst and the support is proposed to increase the oxidation states of Ni and thus contribute to enhancing its intrinsic OER activity. When a Ni catalyst layer is deposited using a carbon-based powder support instead of an expensive Au foil, the overpotential decreased by more than 50 mV at 10 mA/cm(2) due to the synergic effect of the increased surface area and the modified Ni electronic states. In addition, compared with carbon powder supports, Fe and N doped carbon (Fe-N-C) is found to provide particularly more efficient support for the Ni OER catalyst; however, according to electrochemical measurement results, there is no indication of additional Fe intercalation. X-ray photoelectron spectroscopy (XPS) analysis shows the highest binding energy of Ni particularly on the Fe-N-C, suggesting facile electron transfer from Ni to the Fe-N-C interface. (c) 2018 Elsevier Ltd. All rights reserved.
Keywords: OXYGEN EVOLUTION REACTION; LAYERED DOUBLE HYDROXIDE; ELECTROCHEMICAL EVOLUTION; NICKEL FOAM; RAMAN-SPECTROSCOPY; OXIDE CATALYSTS; IRIDIUM OXIDE; COBALT OXIDE; DOPED CARBON; EFFICIENT